DETERMINAN NERACA PERDAGANGAN INDONESIA TAHUN 2000 –2024 - Nova Putri Wulandari; Betty Silfia Ayu Utami (CURVE: Journal of Economic, Business and Accounting, 2026)
The trade balance is one of the key indicators reflecting a country’s economic condition through export and import activities. As one of the world’s leading producers of crude palm oil (CPO), Indonesia relies heavily on CPO exports as a source of foreign exchange. Changes in CPO export volume, international CPO prices, the inflation rate, and the U.S. dollar exchange rate are believed to influence the performance of Indonesia’s trade balance. This study aims to analyze the impact of these four variables on Indonesia’s trade balance in both the short and long term. The study employs a quantitative approach using annual secondary data from 2000 to 2024. The trade balance is used as the dependent variable, while CPO export volume, international CPO prices, inflation, and the U.S. dollar exchange rate serve as independent variables. The analysis was conducted using the Vector Error Correction Model (VECM) to identify short-term and long-term relationships among the variables. The results show that in the short term, none of the variables had a significant effect on Indonesia’s trade balance. Conversely, in the long term, CPO export volume, international CPO prices, inflation, and the U.S. dollar exchange rate had significant effects. CPO exports and prices increase foreign exchange earnings, while inflation reduces export competitiveness. The U.S. dollar exchange rate also affects international trade competitiveness. These findings indicate